Kajian Keputusan Badan Usaha terhadap Kepesertaan Jaminan Kesehatan Nasional di Kabupaten Jember (Corporations Decision on the Involvement in National Health Insurance in Jember) - Galih Dwi Damaiyanti; Eri Witcahyo; Ragil Ismi Hartanti (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Abstract National Health Insurance (NHI) is a part of the National System of Social Insurance which is estabilished by Social Agencies of Health. One of the problems in NHI is corporations membership. All employers such as State-Owned Enterprise (BUMN), large, medium or small scale corporations are the target member of NHI, at least by January 1st 2015, but this target has yet to be actualized. The number of corporation in Jember, by February 2017, has reached 2451 and only 954 corporations were registered (38,92%). The objectives of this study was to assess corporations decision on NHI membership. The study applied qualitative case study. Informant determination technique uses purposive sampling. The results showed that the components of input was not appropriate. Knowledge, perception on product characteristics and need of informants were low, reference group posed significant influence on the corporations decision making in taking part in NHI. The decision making process has yet optimal in the problem or needs analysis and alternative evaluation, corporations tended to be passive in searching information. The output was membership classification of corporations in NHI has yet to be actualized. Key Words : National Health Insurance, Corporation